Radically curable acrylate polyol resin compositions for making quartz-based artificial stones with improved UV radiation resistance and weather resistance

Through the free radical reaction curing technology of block copolymers, the existing acrylate polyol resin has been solved, and the problem of insufficient UV resistance and weather resistance in quartz artificial stone has been achieved, achieving high efficiency, low temperature curing and excellent physical and mechanical properties.

CN119816529APending Publication Date: 2025-04-11CORPORATION HOANG XANH GROUP A&A
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055199.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-15
Filing Date
2023-09-12
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing thermosetting acrylate polyol resins have problems such as insufficient UV resistance and weather resistance, low hardness, long curing time and high temperature in the production of quartz artificial stones.

Method used

The block copolymer of monomers such as n-butyl methacrylate, styrene and hydroxyethyl methacrylate are used to cure radically by oxidation-reduction system of initiators such as dibenzoyl peroxide or dit-butyl peroxide and catalyst-accelerator to form an acrylate polyol resin with excellent UV resistance and weather resistance.

Benefits of technology

It has achieved excellent UV resistance and weather resistance in quartz artificial stone, improved hardness and curing efficiency, reduced curing temperature and time, and met the physical and mechanical properties requirements of artificial stone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816529A_ABST
    Figure CN119816529A_ABST
Patent Text Reader

Abstract

The invention relates to a thermosetting acrylate polyol resin which is synthesized from the block copolymerization of the monomer n-BMA in the range of 51.5% to 60.5% by weight, a styrene monomer in the range of 5% to 15.5% by weight, HEMA or HEA in the range of 33.5% to 46.5% by weight and which is cured by radical reaction with a catalyst-accelerator which is an oxidation-reduction system, and which is characterized in that the weight ratio of the monomer n-BMA in the range of 51.5% to 60.5% by weight, the weight ratio of styrene monomer in the range of 5% to 15.5% by weight, and the weight ratio of HEMA in the range of 33.5% to 46.5% by weight. The present invention relates to an acrylic resin for manufacturing artificial stones to enhance UV resistance and weather resistance, in which an organic peroxide compound is in the range of 0.1 to 5% by weight of the acrylic resin as a catalyst, and a cobalt salt compound or a metal salt compound is in the range of 0.005 to 1% by weight of the acrylic resin as an accelerator. The acrylic resin of the present invention has excellent UV resistance and weather resistance, wherein the color change index [Delta] E * after UV exposure for 1000 hours is less than or equal to 2. An artificial stone product using the acrylate polyol resin composition of the present invention as an adhesive (in the range of 5% to 20% by weight of the mixture) and an inorganic particulate reinforcing agent (in the range of 80% to 95% by weight of the mixture) has physical-mechanical properties meeting technical requirements and excellent UV resistance, wherein the color change index after 1000 hours of UV exposure [Delta] E < = 2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermosetting acrylic polyol resin composition having ultraviolet (UV) radiation resistance and weather resistance, which is synthesized by block copolymerization of monomers of n-butyl methacrylate (n-BMA), styrene, hydroxyethyl methacrylate (HEMA) or 2-hydroxyethyl acrylate (HEA) using dibenzoyl peroxide or di-tert-butyl peroxide or azobisisobutyronitrile as an initiator. The present invention also relates to an artificial stone product, which uses the matrix phase of the acrylic polyol resin of the present invention and is reinforced by quartz granules, and has a flexural strength of 40 to 120 N / mm 2 In the range of 89 to 175 mm deep wear 3 The color change index ΔE≤2 after 1000 hours of UV exposure in an accelerated UV test is particularly good. Background Art

[0002] Acrylic polyol resins are popular thermosetting plastics in the world, which have been studied, produced and applied for decades. Acrylic polymers were first studied by Swiss chemist Georg WA Kahlbaum in 1880. In 1901, in Germany, Otto His work on the synthesis of acrylates was described in "The Polymerization of Acrylic Acid", his doctoral thesis which later led to a patent for the synthesis of this acrylic resin in 1915. Poly(methyl)methacrylate was first marketed in Germany by Rohm and Haas in 1927.

[0003] In order to synthesize thermosetting acrylic polyol resins, different monomers can be used to meet the requirements. The monomers participating in the reaction to form thermosetting acrylic copolymers have different roles, such as monomers methyl methacrylate, styrene, n-butyl methacrylate, 2-ethylhexyl acrylate, hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, butyl acrylate, acrylamide to form acrylic polyol resins with weather resistance, and methyl methacrylate monomers with long substituents to form acrylic resins with water resistance...

[0004] In thermosetting acrylic resin systems, the copolymer obtained has hydroxyl functional groups that participate in direct reactions with curing agents such as isocyanate adducts, amino resins, epoxy resins to form polymers with a steric structure. In this case, it is necessary to use monomers such as hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, butyl acrylate, etc.

[0005] CN103613698A discloses: an acrylic resin having both epoxy functional groups and hydroxyl functional groups, an epoxy equivalent (weight) of 570-630 g / mol, a hydroxyl index of 40-50 mgKOH / g, the acrylic resin containing carboxyl groups, using an amino, isocyanate curing agent at room temperature or heating with a curing agent (ratio within the range of 1-10% by weight of the resin), and their electrostatic coating application. After curing, the coating has very good weather resistance, good flowability, good surface hardness and high gloss, and can be applied to materials of different shapes, or indoor or outdoor building materials.

[0006] US4985517A discloses an acrylic resin formed by copolymerization of a monomer mixture consisting of a hydroxy-substituted (meth) alkyl acrylate, a methacrylate alkyl ester or a vinyl aromatic compound and a higher α-olefin. The document relates to a low molecular weight acrylic resin, which is cured with polyepoxide, diisocyanate, urea formaldehyde, benzoguanamine-aldehyde or melamine-aldehyde at room temperature or 150°C for 1 hour, and is used in an electrostatic coating having UV radiation resistance and weather resistance.

[0007] However, acrylic resins cured by functional groups, such as epoxy resins or melamine formaldehyde resins, have the disadvantages of low hardness, long reaction times and high curing temperatures (150÷180°C), and are therefore not suitable for use in the production technology of artificial stones based on quartz. On the other hand, the presence of aromatic cyclic functional groups from these functional curing agents in the cured acrylic resins leads to poor UV resistance and weathering resistance of the acrylic resins. In order to increase the hardness, reduce the curing time, the curing temperature, and increase the resistance to UV radiation and weathering, the present invention relates to a method for curing acrylic polyol resins according to free radical reactions by catalyst-accelerators (which are oxidation-reduction systems) according to the requirements in the quartz-based artificial paving stone industry. Summary of the invention

[0008] The object of the present invention is to provide a thermosetting acrylic polyol resin cured by free radical reaction, having UV radiation resistance and weather resistance, which is suitable for manufacturing quartz-based artificial stone. The thermosetting acrylic polyol resin of the present invention is synthesized from n-butyl methacrylate (n-BMA) monomer, styrene monomer (SM), hydroxyethyl methacrylate monomer (HEMA) or 2-hydroxyethyl acrylate monomer (HEA) using an initiator of dibenzoyl peroxide or di-tert-butyl peroxide or azobisisobutyronitrile, and is cured by a free radical reaction with a catalyst-accelerator (which is an oxidation-reduction system), which is suitable for the requirements in the quartz-based artificial stone industry.

[0009] Therefore, the present invention provides an acrylic polyol resin having excellent UV radiation resistance and weather resistance, curing by a free radical mechanism, and being used in artificial stone manufacturing, characterized in that:

[0010] i) an acrylic polyol resin having UV radiation resistance and weather resistance, which is synthesized by block copolymerization of n-BMA, SM, HEMA or HEA, wherein:

[0011] √n-BMA in the range of 51.5% to 60.5% by weight;

[0012] √SM is in the range of 5.0% to 15.5% by weight;

[0013] √HEMA or HEA in the range of 33.5% to 45.6% by weight;

[0014] √ an initiator of the curing reaction is in the range of 0.01% to 2% by weight, the initiator of the curing reaction is selected from the following: dibenzoyl peroxide or di-tert-butyl peroxide or azobisisobutyronitrile, calculated by the total weight of the monomer mixture; and

[0015] ii) Acrylic polyols can be cured by free radical reaction with a catalyst of an organic peroxide and an accelerator of a cobalt salt or a manganese salt or a transition metal salt (which is an oxidation-reduction system), wherein:

[0016] √ Organic peroxide selected from the following: tert-butyl peroctanoate; tert-butyl peroxybenzoate; tert-butyl peroxy-3,5,5-trimethylhexanoate; tert-butyl peroxypivalate; tert-butyl peroxy-2-ethylhexanoate; tert-butyl peroxy-isobutyrate; tert-butyl monoperoxy-maleate; tert-butyl peroxy-neoheptanoate; tert-butyl peroxy-neodecanoate; di(4-methylbenzoyl)peroxide; dilauroyl-peroxide; 2,5-dimethyl-2-5-di(2-ethylhexanoylperoxy)hexane; di(3,5,5-trimethyl-hexanoyl)peroxide; tert-amyl peroxy-neodecanoate; 1,1,3,3-tetramethylbutyl peroxy-neodecanoate, calculated by the weight of the acrylic polyol resin in the range of 0.1 to 5% by weight, and

[0017] √ The accelerator is selected from the following: cobalt (II) salt compounds such as cobalt octoate, manganese salts, or metal salt compounds, etc., calculated by the weight of the acrylic polyol resin in the range of 0.005% to 1% by weight;

[0018] (iii) The acrylic polyol resin of the present invention has the following characteristics: solid content in the range of 40% to 80%; color according to Hazen scale ≤ 10; liquid density in the range of 1.01 to 1.2 g / cm at a temperature of 23° C. and a relative humidity of 57% 3in the range of 500 to 1000 mPa.s at a temperature of 23°C; a tensile strength in the range of 40 to 60 MPa; a flexural strength in the range of 60 to 120 MPa; a Barcol hardness in the range of 40 to 55; resistance to UV radiation and weathering, wherein the color change index ΔE≤2 after 1000 hours of UV exposure in an accelerated UV test according to ASTM G154-06:2006 standard.

[0019] The present invention also provides a quartz-based artificial stone product using a matrix phase of the acrylic polyol resin of the present invention in the range of 5 to 20% by weight and a reinforcing agent (which is an inorganic compound) in the range of 80 to 95% by weight, wherein:

[0020] √ Quartz, cristobalite, sand and sand or glass derivative materials having a particle size less than 0.045 mm in the range of about 10% to 37.5% by weight, based on the total weight of the mixture;

[0021] √ Quartz, cristobalite, sand and sand or glass derivative materials with a particle size of 0.045 mm to 0.1 mm in the range of 15 to 42.5% by weight based on the total weight of the mixture;

[0022] √ Quartz, cristobalite, sand and sand or glass derivative materials with a particle size of 0.1÷0.5 mm in the range of 10% to 37.5% by weight, calculated on the total weight of the mixture;

[0023] √ Quartz, cristobalite, sand and sand or glass derivative materials with a particle size of 0.5÷2.5 mm in the range of 17.5% to 45.6% by weight, calculated on the total weight of the mixture;

[0024] √ Quartz, cristobalite, sand and sand or glass derivative materials with a particle size of 2.5÷6.0 mm in the range of 20% to 47.5% by weight, calculated on the total weight of the mixture;

[0025] The artificial stone product using the acrylic polyol resin of the present invention as the matrix phase has physical-mechanical properties: i) flexural strength of 40 to 120 N / mm 2 ii) Deep wear is between 89 and 175 mm 3 iii) water absorption in the range of 0.01% to 0.05%; iv) impact resistance ≥ 3J; v) particularly excellent UV resistance, wherein the color change index ΔE≤2 after 1000 hours of UV exposure in an accelerated UV test. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1: Thermally cured acrylic resin before (1) and after (2) curing by free radical reaction.

[0027] FIG. 2 : FTIR spectra showing the chain-sticking ability of acrylic polyol resins (Sample 1, Sample 2, and Sample 4 are control samples, and Sample 3 is a sample of the present invention).

[0028] Figure 3: TGA and DTG curves of acrylic polyol resin sample after curing and burning under atmospheric conditions.

[0029] Figure 4: FTIR spectra of free radical reaction cured acrylic resin (Sample 1) before and after 1000 hours of UV exposure in an accelerated UV test (control sample).

[0030] Figure 5: FTIR spectra of free radical reaction cured acrylic resin (Sample 2) before and after 1000 hours of UV exposure in an accelerated UV test.

[0031] Figure 6: FTIR spectra of free radical reaction cured acrylic resin (Sample 3) before and after 1000 hours of UV exposure in an accelerated UV test.

[0032] Figure 7. FTIR spectra of free radical reaction cured acrylic resin (Sample 4) before and after 1000 hours of UV exposure in an accelerated UV test.

[0033] FIG. 8 . Surface images of artificial stone products using a matrix phase of acrylic resin - Sample 1, Sample 4 (control sample) after curing (a, b) and after polishing (c).

[0034] Figure 9: Surface images of artificial stones using matrix phases of acrylic resin - sample 3 (invention) and PEKN resin (control sample) after curing (a) and after polishing (b).

[0035] Figure 10: Color change of artificial stone products using a matrix phase of acrylic polyol resin (Sample 1, Sample 2, Sample 3 and Sample 4) and unsaturated polyester resin (UPR) after 1000 hours of UV exposure in an accelerated UV test.

[0036] Figure 11: Scanning electron microscopy (SEM) images of an artificial stone sample using an acrylic polyol resin (Sample 2) at 500 times magnification before (a) and after (b) 1000 hours of UV exposure in an accelerated UV test.

[0037] Figure 12: SEM images of an artificial stone sample using a matrix resin (Sample 4) at 500x magnification before (a) and after (b) 1000 hours of UV exposure in an accelerated UV test.

[0038] Figure 13: SEM images of artificial stone samples using matrix UPR resin at 500x magnification before (a) and after (b) 1000 hours of UV exposure in an accelerated UV test.

[0039] FIG. 14 : SEM images of an artificial stone sample using resin sample 3 at 500 times magnification before (a) and after (b) 1000 hours of UV exposure in an accelerated UV test. DETAILED DESCRIPTION

[0040] The UV radiation resistant and weather resistant acrylic polyol resin as described in the present invention is an acrylic polyol resin synthesized by block copolymerization of monomers n-butyl methacrylate (n-BMA), styrene monomer (SM), hydroxyethyl methacrylate (HEMA) or 2-hydroxyethyl acrylate (HEA). The block copolymerization of the monomers forms the acrylic polyol resin according to the following scheme:

[0041] In the present invention, n-butyl methacrylate (n-BMA) is used as the first monomer acrylate in the range of 51.5 to 60.5% by weight in order to improve gloss, hardness, flexibility in the resin and improve UV resistance and weather resistance of the obtained acrylic resin.

[0042] Hydroxyethyl methacrylate (HEMA) or 2-hydroxyethyl acrylate (HEA) is used as the second monomer acrylate in the range of 33.5% to 45.6% by weight to improve elasticity, provide polarized groups OH-, which help the synthesized acrylic resin to react with the isocyanate adduct to generate crosslinking. This helps improve the UV resistance and weather resistance of the obtained acrylic resin in outdoor applications.

[0043] According to the present invention, the use of styrene monomer in the range of 5.0% to 15.5% by weight targets the impact resistance, weather resistance and increased hydrophobicity of the resin. Styrene also enables the crosslinking of the chains in the chain of the acrylic polyol resin to occur faster and more thoroughly in the presence of an organic peroxide catalyst and an accelerator such as a cobalt salt or a manganese salt.

[0044] According to the present invention, the finished acrylic polyol resin is cured by free radical reaction with a catalyst-accelerator (which is an oxidation-reduction system), the free radicals being formed by the following reaction mechanism:

[0045]

[0046] The curing reaction of the heat-curable acrylic polyol copolymer forms a polymer having a three-dimensional structure as shown in FIG. 1 .

[0047] According to the present invention, the catalyst used in the curing of the finished acrylic polyol resin is an organic peroxide compound such as: tert-butyl peroctanoate; tert-butyl peroxybenzoate; tert-butyl peroxy-3,5,5-trimethylhexanoate; tert-butyl peroxy-pivalate; tert-butyl peroxy-2-ethylhexanoate; tert-butyl peroxy-isobutyrate; tert-butyl monoperoxy-maleate; tert-butyl peroxy-neoheptanoate; tert-butyl peroxy-neodecanoate; di(4-methylbenzoyl)peroxide; dilauroyl-peroxide; 2,5-dimethyl-2-5-di(2-ethylhexanoylperoxy)hexane; di(3,5,5-trimethyl-hexanoyl)peroxide; tert-amyl peroxy-neodecanoate; 1,1,3,3-tetramethylbutyl peroxy-neodecanoate, calculated by the weight of the acrylic polyol resin, in the range of 0.1 to 5%;

[0048] According to the present invention, the accelerator used in the curing of the acrylic polyol resin is a cobalt (II) salt compound such as cobalt octoate, or a manganese salt, or a metal salt compound, etc., in the range of 0.005% to 1% by weight of the acrylic polyol resin.

[0049] In the present invention, the curing temperature of the free radical curing acrylic polyol resin is in the range of 80°C to 180°C.

[0050] In the present invention, the curing time of the free radical-cured acrylic polyol resin is in the range of 30-120 minutes.

[0051] The finished acrylic polyol resin of the present invention meets the requirements of the quartz-based artificial stone manufacturing industry and has the technical characteristics as shown in Table 1:

[0052] Table 1: Mechanical property requirements of acrylic polyol resins

[0053]

[0054] According to the present invention, the artificial stone product uses an acrylic polyol resin binder in a range of 5 to 20% by weight and an inorganic particulate reinforcing agent in a range of 80 to 95% by weight.

[0055] The properties of artificial stone depend on the distribution of aggregate particle size and their ratio in its composition. The basic formulation of granular aggregate includes large particle size (from 0.1mm or larger) and fine particles (less than 0.045mm). The preferred embodiment of granular aggregate mixture is to contain particles with large particle size and particles with small particle size in an optimized ratio. The optimized formulation is that the granular aggregate used must be optimized to ensure the most compact arrangement of aggregate particles and produce the dense structure of the resulting material. Therefore, in the present invention, granular aggregate with different particle sizes is used as follows:

[0056] - quartz, cristobalite, sand and sand or glass derivative materials with a particle size less than 0.045 mm in the range of 10 to 37.5% by weight of the mixture;

[0057] - quartz, cristobalite, sand and sand or glass derivative materials with a particle size of 0.045 mm to 0.1 mm in the range of 15 to 42.5% by weight of the mixture;

[0058] - quartz, cristobalite, sand and sand or glass derivative materials with a particle size of 0.1÷0.5 mm in the range of 10 to 37.5% by weight of the mixture;

[0059] - quartz, cristobalite, sand and sand or glass derivative materials with a particle size of 0.5÷2.5 mm in the range of 17.5% to 45.6% by weight, calculated on the total weight of the mixture;

[0060] - quartz, cristobalite, sand and sand or glass derivatives with a particle size of 2.5÷6.0 mm in the range of 20% to 47.5% by weight of the mixture;

[0061] In the present invention, the curing temperature of the artificial stone product (using the matrix phase of the acrylic polyol resin and the inorganic granular aggregate as a reinforcing agent) is in the range of 80°C to 180°C.

[0062] In the present invention, the curing time of the artificial stone product (using the matrix phase of the acrylic polyol resin and the inorganic granular aggregate as a reinforcing agent) is in the range of 30 to 120 minutes.

[0063] According to the present invention, the quartz-based artificial stone product (using the matrix phase of acrylic polyol resin and inorganic granular aggregate as reinforcing agent) has several properties as shown in Table 2:

[0064] Table 2: Physical and mechanical properties of artificial stone products using acrylic polyol resins

[0065]

[0066]

[0067] Example

[0068] The present invention is illustrated by the following examples, which should not be construed as limiting the scope of the invention in any way.

[0069] Example 1: Synthesis of 1000 g of acrylic acid polyol resin

[0070] Control samples and samples of the invention were prepared as shown below.

[0071]

[0072] 1000 g of sample 1 (control sample, using a styrene content of less than 5% by weight of the reaction mixture) synthesized from the following components: 620.68 g of n-BMA (54.24% by weight), 378.82 g of HEMA (37.88% by weight), initiator is azobisisobutyronitrile (AIBN) 0.5 g (0.05% by weight). The finished acrylic polyol resin sample 1 obtained by curing by adding 2% by weight (calculated by the weight of the finished acrylic polyol resin) of tert-butyl peroxy-3,5,5-trimethylhexanoate as a catalyst and 0.02% by weight (calculated by the weight of the acrylic polyol resin) of cobalt tethylhecxaoctoate solution (wherein the concentration is 10% by weight in naphthalene solvent) as an accelerator was used to determine the curing parameters.

[0073] 1000 g of sample 2 (control sample, using a styrene content higher than 15.5% by weight) synthesized from the following components: 396.92 g of n-BMA (39.69% by weight), 219.12 g of styrene (29.11% by weight of the reaction mixture), 311.46 g of HEMA (31.15% by weight of the reaction mixture), initiator is azobisisobutyronitrile (AIBN) 0.5 g (0.05% by weight of the reaction mixture). The finished acrylic polyol resin sample 2 was cured by adding 2% by weight (calculated by the weight of the finished acrylic polyol resin) of tert-butyl peroxy-3,5,5-trimethylhexanoate as a catalyst and 0.02% by weight (calculated by the weight of the finished acrylic polyol resin) of cobalt ethylhexanoate solution (wherein the concentration in naphthalene solvent is 10% by weight) as an accelerator for determining the curing parameters.

[0074] 1000 g of sample 3 (inventive) synthesized from the following components: 537.11 g of n-BMA (53.71% by weight of the reaction mixture), 118.18 g of styrene (11.82% by weight of the reaction mixture), 344.21 g of HEMA (34.42% by weight of the reaction mixture), initiator is azobisisobutyronitrile (AIBN) 0.5 g (0.05% by weight of the reaction mixture). The acrylic polyol resin sample 3 obtained by curing by adding 2% by weight (calculated by the weight of the finished acrylic polyol resin) of tert-butyl peroxy-3,5,5-trimethylhexanoate as a catalyst and 0.02% by weight (calculated by the weight of the finished acrylic polyol resin) of cobalt ethylhexanoate solution (wherein the concentration in naphthalene solvent is 10% by weight) as an accelerator was used to determine the curing parameters.

[0075] 1000 g of sample 4 (control sample) was synthesized from the following components: 537.11 g of n-BMA (53.71% by weight of the reaction mixture), 118.18 g of styrene (11.82% by weight of the reaction mixture), 344.21 g of HEMA (34.42% by weight of the reaction mixture), and the initiator was 0.5 g of azobisisobutyronitrile (AIBN) (0.05% by weight of the reaction mixture). The finished acrylic polyol resin sample 4 was cured with 30% by weight of melamine formaldehyde resin, and the catalyst was p-toluenesulfonic acid (PTSA) at a ratio of 1% by weight, calculated by the total weight of the acrylic resin and the melamine formaldehyde resin, and the resin sample was cured at 150° C. for determining the curing parameters.

[0076] The reaction mixture of the materials was charged into a 2 liter four-necked glass flask and copolymerized in an inert gas atmosphere (N2) at a temperature ranging from 40° C. to 70° C. The reaction time was 5 hours until the viscosity of the reaction mixture at 70° C. was in the range of 300-400 cP, and then stopped.

[0077] In order to determine the physical and mechanical properties of the acrylic polyol resin products after curing, the resin samples were prepared according to the above method, however, after mixing with the catalyst-accelerator, the liquid resin mixture was formed into samples by pouring the liquid resin mixture into a mold according to the corresponding standard and heating at 100°C for 60 min for Sample 1, Sample 2, Sample 3 and at 150°C for 60 min for Sample 4.

[0078] Tables 3 and 4 show the technical parameters and physical and mechanical properties of the acrylic resin after curing.

[0079] Table 3: Several technical parameters of liquid acrylic polyol resin products

[0080]

[0081] Table 4: Several physical and mechanical properties of the acrylic polyol resin product of Example 1 after curing

[0082]

[0083] Table 3 shows that Sample 2 and Sample 3 use styrene monomer in the reaction mixture and are cured by free radical reaction, and then the technical parameters and physical-mechanical properties of the liquid acrylic polyol resin sample and the acrylic polyol resin after curing are almost the same. For Sample 1, no styrene is used in the reaction mixture, and the technical parameters and physical-mechanical properties of the liquid resin and the resin after curing are lower than those of Sample 2 and Sample 3. Specifically, for Sample 1, the liquid resin is yellowish in color after synthesis, the solid content is 14% lower than that of Sample 2 and Sample 3, and the curing time lasts 30 minutes longer than that of Sample 2 and Sample 3. For Sample 4, after curing, the obtained finished acrylic polyol resin is cured by functional group reaction, and the gelation time and curing time last 20 minutes longer than Sample 3, and the maximum exothermic temperature is 38°C lower than that of Sample 3.

[0084] Table 4 shows the physical-mechanical properties of acrylic polyol resin sample 1 after curing, which has a 40% lower Barcol hardness, a 37.7% lower tensile strength, a 34% lower flexural strength, and a 30% higher wear than sample 2 and sample 3. For sample 4, the physical and mechanical properties of acrylic polyol resin after curing have a 20% lower Barcol hardness, a 31.7% lower tensile strength, a 23% lower flexural strength, and a 23% higher wear than sample 3. Therefore, styrene has an influence on the chain bonding ability of acrylic polyol resin when cured by free radical reaction. The resulting free radical cured acrylic polyol resin has better physical and mechanical properties than functional group cured polyol acrylic resin.

[0085] Evaluation of the chain bonding ability of the acrylic polyol resin by free radical reaction and the acrylic polyol resin by functional group reaction using an organic peroxide as a catalyst and cobalt octoate as an accelerator was performed via Fourier transform infrared spectroscopy (FTIR), wherein the results are shown in FIG. 2 .

[0086] FIG. 2 shows that when the acrylic resin is cured by free radical reaction (Sample 2, Sample 3), the resin sample no longer shows the 1639 cm-1 characteristic of the C=C bond in the acrylate monomer and the monomer containing the hydroxyl functional group. -1 and 815cm -1This proves that the double bonds of the residual monomers in the acrylic resin after synthesis fully participate in the curing reaction. On the other hand, for sample 1, in addition to the 1721 cm -1 The peak at 1147 cm representing the COC stretching oscillation -1 There is also a peak at 1639cm -1 and 815cm -1 This proves that the chain bonding process of the acrylic resin does not occur completely, and the residual monomers have not yet completely participated in the cross-linking formation after block copolymerization.

[0087] When the acrylic polyol resin is cured by functional group reaction (curing by melamine formaldehyde - Sample 4), the FTIR spectrum of the acrylic resin after curing shows a 1639 cm-1 characteristic of the C=C bond in the acrylate monomer and the monomer containing the hydroxyl functional group. -1 and 815cm -1 In addition to the peak at 1721 cm -1 The peak at 1143 cm representing the COC stretching oscillation -1 The peak at 750 cm representing the CH bond in benzene -1 The acrylic resin cured by functional group reaction also has a peak at 1550cm -1 The peak at and the peak in melamine formaldehyde (sample 4).

[0088] Example 2: Evaluation of heat resistance of the finished acrylic polyol resin after curing by thermogravimetric analysis (TGA)

[0089] Acrylic resin samples (Sample 1, Sample 2, and Sample 4) were used as control samples and the acrylic polyol resin sample of the present invention of Example 1 (Sample 3).

[0090] The heat resistance of the finished acrylic polyol resin after curing was evaluated by a French TGI 600 Setagram in non-isothermal mode (temperature increased from room temperature to 800°C at a rate of 10°C / min) with an air flow of 2.5 l / h. A 10 ml platinum crucible was used. The heat resistance of the finished acrylic polyol resin sample after curing is shown in Table 5 and Figure 3:

[0091] Table 5: Heat resistance of acrylic polyol resin after curing

[0092] sample <![CDATA[T 10 ,℃]]> <![CDATA[T 50 ,℃]]> <![CDATA[T 1max ,℃]]> <![CDATA[T 2max ,℃]]> Ash content at 800℃, % Sample 1 319.30 408.84 450.38 640.18 0.22 Sample 2 348.24 417.23 450.78 642.35 0.25 Sample 3 364.70 426.99 451.9 655.27 2.86 Sample 4 289.93 384.06 448.38 594.27 0.21

[0093] Where: T 10 - Temperature at which weight loss is 10%, T 50 - Temperature at which weight loss is 50%, T 1max- The temperature at which the weight loss rate is maximum in stage 1, T 2max -The temperature at which the rate of weight loss is maximum during this stage.

[0094] Figure 3 shows that at 200°C, the evaporation of water and the original substance does not participate in the reaction. The decomposition of stage 1 starts at 200°C and occurs relatively quickly from 300°C to 500°C, and the total weight loss in this stage is 90% by weight. In this stage, the crosslinks formed by the acrylic acid monomer and the acrylic ester polyol molecular chain are broken, and then the acrylic ester polyol main chain is broken to form the pyrolysis product.

[0095] In stage 2, which occurs at greater than 500° C., the weight is burned. This indicates thermal destruction in the presence of oxygen, which produces combustion products.

[0096] From the results in Table 5, it can be seen that compared with samples 1 and 2, the T 10 、T 50 、T 1max 、T 2max The ash content of sample 3 was increased by 15 to 61°C, and the ash content of sample 3 was 92% higher than that of sample 2 and sample 1. On the other hand, the T of sample 3 cured according to the present invention was higher than that of sample 4 cured by functional group reaction. 10 、T 50 、T 2max 42°C ÷ 75°C higher, the ash content in sample 3 obtained was 92% higher than that in sample 4. This proves that sample 3 cured by free radical reaction is thermally stable and has the best resistance to UV radiation and weathering.

[0097] Example 3: Evaluation of the UV resistance of acrylic polyol resin samples (Sample 1÷Sample 4 of Example 1) after curing.

[0098] The weather resistance and UV radiation resistance of acrylic resins were carried out according to ASTM G154-06:2006: Standard for fluorescent light-emitting devices for non-metallic materials exposed to radiation. The test was carried out on a time accelerometer (product of ATLAS, USA) with four climate simulation modes: UV radiation (340nm), moist heat generation, rain spray and dark conditions. The test conditions include external light (340nm); wavelength: 340nm; radiation energy: 0.89W / m2; test cycle: 8 hours of UV radiation at a temperature of 60±3℃, and 4 hours of condensation at a temperature of 50±3℃.

[0099] According to the reflection principle, the physical and mechanical properties and color changes of the resin samples (including sample 1, sample 2, sample 3 and sample 4) obtained from the acrylic resin sample in Example 1 before UV irradiation (0 hour) and after UV irradiation (1000 hours) were measured on the American Xrite colorimeter Xrite C17800 under the above conditions.

[0100] Colorimetry by reflection principle, using color space CIELab; L*; a*; b*; ΔE*, according to ASTM E313-10:2010.

[0101] The physical and mechanical properties and color changes of the acrylic polyol resin samples before and after UV irradiation are shown in Tables 6 and 7.

[0102] Table 6: Deterioration of physical and mechanical properties of acrylic polyol resin samples after irradiation with UV for 1000 hours

[0103]

[0104] Table 6 shows that after 1000 hours of UV exposure, the physical-mechanical properties of Sample 1, Sample 2 and Sample 4 (control sample) showed significant decreases, while Sample 3 showed a slight decrease. Specifically, after 1000 hours of UV exposure, compared with the sample before UV irradiation, the Barcol hardness decreased by 64% in Sample 1, 47% in Sample 2, 12.5% ​​in Sample 3, and 50% in Sample 4; the tensile strength decreased by 60% in Sample 1, 24% in Sample 2, 11% in Sample 3, and 42.8% in Sample 4; the flexural strength decreased by 55% in Sample 1, 26% in Sample 2, 3.5% in Sample 3, and 41.8% in Sample 4; the abrasion increased by 33% in Sample 1, 25% in Sample 2, 12.5% ​​in Sample 3, and 40% in Sample 4. Therefore, Sample 3 of the present invention is more thermally stable, UV-resistant, and weather-resistant than Samples 1, 2, and 4.

[0105] Table 7: Color change of acrylic polyol resin samples after 1000 hours of UV exposure

[0106] parameter Sample 1 Sample 2 Sample 3 Sample 4 ΔE* 10.65 4.86 1.55 11.62

[0107] Table 7 shows that the color changes of the control samples (Sample 1, Sample 2, and Sample 4) after UV exposure showed obvious color changes, i.e., after 1000 hours of UV exposure, the color index ΔE* of Sample 1 was 10.65, Sample 2 was 4.86, and Sample 4 was 11.62. Meanwhile, the color index ΔE* of Sample 3 (of the present invention) showed a value of 1.55, which was 6.8 times lower than that of Sample 1, 3.14 times lower than that of Sample 2, and 7.5 times lower than that of Sample 4. Therefore, the free radical curing mechanism of the present invention helps to improve the UV radiation resistance of the acrylic polyol resin.

[0108] This can be explained as follows: In sample 1, the hardened acrylic resin obtained by free radical reaction has a slow and incomplete chain bonding process. Under the action of UV radiation, the unstable double bond -C=C- remaining in the monomer and acrylic copolymer is easily destroyed to form a chromophore, so the color of sample 1 changes dramatically. In sample 2, due to the high content of styrene in the molecular structure of the hardened acrylic resin, the -C=C- bond in the aromatic ring has a π electron vibration plane located perpendicular to the bond, which leads to the formation of an unstable bond. This bond is easily decomposed and converted into a colored ketone group (-C=O-) under UV exposure. The more these unstable -C=C- bonds are in the resin molecular chain, the easier it is to break, and the color change of the resin sample (sample 2) is significant. In sample 4, melamine formaldehyde is used as a thermal curing agent and p-toluenesulfonic acid as a catalyst to cure the acrylic polyol resin through a functional group mechanism. Among them, the melamine formaldehyde curing agent has an unstable double bond (-C=C-) in the aromatic ring, which causes the polymer chain to be easily destroyed under the action of UV irradiation.

[0109] FTIR spectra of the cured resin samples (including Sample 1, Sample 2, Sample 3, and Sample 4) after UV irradiation are shown in FIGS. 4 , 5 , 6 , and 7 .

[0110] FIG4 shows the FTIR infrared spectra of an acrylic resin cured by a functional group reaction (Sample 1 is a control sample) before UV irradiation (0 hours) and after UV irradiation (1000 hours) on a time-accelerated ultraviolet radiation test device. As shown in FIG4, after 1000 hours of UV irradiation, the peak intensities at 1639 cm-1 and 815 cm-1, which characterize the -C=C- bond in the acrylic resin, are sharply reduced, and this indicates thermal aging in the molecular structure of the cured acrylic resin. On the other hand, the peak intensities at 1721 cm-1, which characterizes the C=O bond, and 1147 cm-1, which characterizes the CO bond, are both significantly reduced, indicating that the ester bond is broken due to photo-oxidation to form a new bond.

[0111] FIG5 shows the FTIR spectra of the acrylic resin cured by functional group reaction (sample 2 is a control sample) before UV irradiation (0 hours) and after UV irradiation (1000 hours) on a time-accelerated ultraviolet radiation test device. As shown in FIG5, after 1000 hours of UV irradiation, the peak intensities at 1721 cm-1 representing the C=O bond and 1147 cm-1 representing the CO bond are both significantly reduced, indicating that the ester bond is broken due to photo-induced oxidation to form a new bond. In addition, the absorption peak at 750 cm-1 representing the bending vibration of the CH bond in the benzene ring is significantly reduced, indicating thermal aging in the structure of the acrylic resin.

[0112] FIG6 shows the FTIR spectra of an acrylic resin (sample 3 of the present invention) cured by free radical reaction before UV irradiation (0 hours) and after 1000 hours of UV exposure in a UV test. As shown in FIG6 , after 1000 hours of UV irradiation, the peak intensities at 1721 cm-1 representing the C=O bond and 1147 cm-1 representing the CO bond did not decrease significantly compared to the acrylic sample before UV irradiation. In addition, the absorption peak at 750 cm-1 representing the CH bond in the benzene ring almost overlaps with the FTIR spectrum of the resin sample before UV irradiation. Therefore, it can be seen that the acrylic resin cured by free radical reaction has better UV radiation resistance and weather resistance than the acrylic resin cured by functional groups.

[0113] FIG7 shows the FTIR infrared spectra of an acrylic resin cured by a functional group reaction (sample 4 is a control sample) before UV exposure in a UV test (0 hours) and after UV exposure for 1000 hours. As shown in FIG7 , after 1000 hours of UV exposure, the peak intensities of all functional groups dropped sharply, wherein the peak intensities at 1639 cm-1 and 815 cm-1 characterize the C=C bond in the acrylic resin, the peak at 1550 cm-1 characterizes the C=N bond in the nitrogen-containing heterocycle, and the peak at 750 cm-1 characterizes the CH bond in the benzene ring. This indicates thermal aging in the molecular structure of the cured acrylic resin. On the other hand, the peak intensities at 1721 cm-1 characterizing the C=O bond and 1143 cm-1 characterizing the CO bond both decreased significantly, indicating that the ester bond was broken due to photo-oxidation to form a new bond.

[0114] Example 4: Effect of the acrylic polyol resin of Example 1 on the processability, physical and mechanical properties of a quartz-based artificial stone product.

[0115] Artificial stone samples were manufactured in the laboratory using the acrylic resin samples of Example 1 (Sample 1, Sample 2 and Sample 4), the unsaturated polyester resin (UPR) and the acrylic ester polyol resin sample of the present invention of Example 1 (Sample 3), wherein the unsaturated polyester resin (UPR) was cured by adding a catalyst of tert-butyl peroxy-3,5,5-trimethylhexanoate at a ratio of 2% by weight (relative to the weight of the UPR resin) and a 10% by weight cobalt ethylhexanoate solution in a naphthalene solvent at a ratio of 0.02% by weight (relative to the UPR resin) as an accelerator (as a control sample).

[0116] The artificial stone samples based on quartz were manufactured by vibration pressing in vacuum technology and heat cured at a temperature of 130° C. for 60 minutes for samples 1, 2, 3 and UPR and at 150° C. for 60 minutes for sample 4, with dimensions of 300×300×20 (mm). The total weight of the materials used to manufacture the artificial stone samples was 5000 g. Among them, the components of the mixture for making the artificial stone sample include 625g of resin (12.5% ​​by weight of the whole material), the resin sample already includes 2.0% by weight of 3-(trimethoxysilyl)propyl methacrylate and the catalyst-accelerator (curing agent) according to Example 1; 1200g of cristobalite powder with a particle size of ≤0.045mm (24% by weight of the whole material); 1050g of cristobalite aggregate with a particle size in the range of 0.1÷0.4mm (21% by weight of the whole material); 1100g of quartz aggregate with a particle size in the range of 0.1÷0.4mm (22% by weight of the whole material); 925g of quartz aggregate with a particle size in the range of 0.3÷0.7mm (18.5% by weight of the whole material) and 100g of TiO2 powder (2.0% by weight of the whole material).

[0117] The manufacturability and physical-mechanical properties of the artificial stone products using the above composition are shown in FIG8 , FIG9 , Table 8 and Table 9:

[0118] Table 8: Comparison of the producibility of artificial stone samples using different resin binders

[0119]

[0120] The curing time of the artificial stone product using the matrix phase of acrylic resin sample 1 (control sample) is 30 minutes longer than sample 2, sample 3 and UPR resin. Sample 1 and sample 4 are less flexible, dry after vibration, and the stone sample after curing has a blistering surface, surface scratches and poor gloss after grinding (Figure 8 and Table 8). Sample 2, sample 3 and UPR sample have similar curing times, are flexible after vibration, and have no surface scratches after polishing (Figure 9 and Table 8).

[0121] Table 9: Effect of matrix resin on the physical-mechanical properties of artificial stone products

[0122]

[0123]

[0124] Table 9 shows that the flexural strength of the artificial stone product using the matrix phase of the acrylic polyol resin sample 3 (of the present invention) is 50% higher than that of sample 1, 9.6% higher than that of sample 2, and 27.4% higher than that of sample 4; the water absorption rate is reduced by 71% compared with sample 1, 25% compared with sample 2, 56% compared with sample 4, and 9% compared with the artificial stone sample using the UPR resin. This proves that the artificial stone product using the acrylic polyol resin binder of this patent has better and more specific adhesion between aggregate particles than other resin binders, so the physical-mechanical properties of the obtained artificial stone product based on acrylic polyol resin are enhanced.

[0125] Example 5: Evaluation of UV and Weathering Resistance of Quartz-Based Artificial Stone Samples

[0126] The quartz-based artificial stone products using the acrylic resin of Example 1 (Sample 1, Sample 2 and Sample 4), the unsaturated polyester resin (UPR) of Example 4 were control samples, and the acrylic ester polyol resin sample of the present invention (Sample 3) of Example 1 was used to manufacture artificial stone samples in the laboratory.

[0127] These artificial stone products used the ratios of cristobalite granular aggregate, quartz granular aggregate and resin in Example 4.

[0128] Artificial stone samples with a size of 300x80x20 (mm) after manufacture and polished (gloss ≥ 50 GU) on their surfaces were tested for weather resistance and UV radiation resistance according to ASTM G154-06:2006, and the color change was evaluated according to ASTM E313-10:2010 (as described in Example 2), and the surface gloss was measured according to ISO 2813:1994: Standard for determining the gloss of metallic materials, on a gloss meter IG 320 from Hor iba, Japan, at a measuring angle of 60° for medium gloss material surfaces (gloss in the range of 10÷70 GU).

[0129] The changes in physical and mechanical properties of the artificial stone product using the matrix resin and UPR resin of Example 1 are shown in Table 10.

[0130] Table 10: Physical and mechanical properties of artificial stone products using different resin binders before UV exposure (0 hours) and after 1000 hours of UV exposure

[0131]

[0132] As can be seen from Table 10, after 1000 hours of UV exposure, sample 3 (of the present invention) has no significant changes in physical and mechanical properties compared to the samples before UV exposure. However, the artificial stone samples using the adhesive in UPR resin, sample 1, sample 2 and sample 4 have significant reductions in physical-mechanical properties after 1000 hours of UV exposure. Among them, the flexural strength in the UPR sample decreased by 16%, in sample 1 by 30%, in sample 2 by 12%, and in sample 4 by 22.6% compared to the properties before UV exposure, respectively; the water absorption increased by 34% in the UPR adhesive, by 36% in sample 1, by 25% in sample 2, and by 33.8% in sample 4, respectively, compared to the properties before UV exposure; the impact resistance decreased by 14% in the UPR adhesive, by 50% in sample 1, by 14% in sample 2, and by 40% in sample 4, respectively, compared to the properties before UV exposure. This proves that after 1000 hours of UV exposure, the surface of the stone product using resin sample 3 was not damaged, and the dense structure resulted in almost unchanged physical-mechanical properties. In the artificial stone products using the matrix resins of samples 1, 2, and 4 and the UPR resin, after 1000 hours of UV exposure, the surface of the stone product was damaged, resulting in a non-dense structure, which reduced the physical-mechanical properties.

[0133] The color and gloss changes of the artificial stone surface using the base acrylic resin and the UPR resin of Example 1 (associated with the UV irradiation time after 500 hours and 1000 hours) are shown in Table 11.

[0134] Table 11: Color change (ΔE*) and gloss of artificial stone surfaces using acrylic polyol resin (Example 1) and UPR resin as a function of UV exposure time

[0135]

[0136] As shown in Table 11 and FIG. 10 , the artificial stone samples using the acrylic resin and the UPR resin of Sample 1, Sample 2, and Sample 4 have obvious discoloration and a rapid decrease in glossiness, especially in Sample 1. For UPR, the color change ΔE* after 500 hours and 1000 hours of UV exposure was 5.72 and 8.92, respectively, and the gloss decreased by 15GU and 23GU after 500 hours and 1000 hours of UV exposure, respectively; for acrylic resin sample 1, the color change ΔE* was 7.48 and 10.63, respectively, and the gloss decreased by 20GU and 26GU after 500 hours and 1000 hours of UV exposure, respectively; for acrylic resin sample 2, the color change ΔE* was 2.01 and 4.52, respectively, and the gloss decreased by 13GU and 20GU after 500 hours and 1000 hours of UV exposure, respectively; for acrylic resin sample 4, the color change ΔE* was 6.28 and 9.22, respectively, and the gloss decreased by 17GU and 24GU after 500 hours and 1000 hours of UV exposure, respectively.

[0137] Meanwhile, the artificial stone sample using the acrylic polyol matrix resin of the present invention (Sample 3) has a small change in the color and gloss of the stone surface after 1000 hours of UV exposure. Under the same UV exposure time of 500 hours and 1000 hours, the color change ΔE* of Sample 3 of the present invention is 10÷25 times lower than that of the matrix resin and UPR resin using Samples 1, 2, 4.

[0138] In order to evaluate the effect of UV irradiation on the structural morphology of the artificial stone samples using the acrylic resin of Example 1, scanning electron microscopy (SEM) images of the artificial stone samples were taken before UV irradiation (0 hours) and after UV irradiation (1000 hours). SEM images of artificial stone samples using UPR resin (control sample), acrylic resin of Example 1 (sample 2, sample 4-control sample and sample 3 of the present invention) at 500 times magnification are shown in Figures 11 to 14.

[0139] Figures 11, 12, and 13 show that before UV irradiation, the artificial stone samples using the acrylic polyol resin and UPR resin of Sample 2 and Sample 4 had a dense structure in which the matrix resin was tightly bonded to the quartz granular aggregate (Figures 11a, 12a, and 13b). However, after UV irradiation for 1000 hours on a time accelerometer, the surface of the artificial stone aged and the bond between the matrix resin and the granular aggregate was destroyed (Figures 11b, 12b, and 13b).

[0140] Figure 14 shows that before UV irradiation, the artificial stone sample using the acrylic polyol resin of the present invention (sample 3) has a dense structure in which the matrix resin is tightly combined with the granular aggregate (Figure 14a). After irradiating UV for 1000 hours, the surface of the artificial stone is almost undamaged (Figure 14b), indicating that the combination between the matrix resin and the granular aggregate is tightly combined, and the dense material structure is shown by the reduction and discoloration of the gloss on the surface of the artificial stone product (Table 4). This result confirms that the artificial stone sample using the acrylic polyol resin cured by the free radical reaction of the present invention has excellent UV resistance and weather resistance.

[0141] Advantageous Effects of the Invention

[0142] Unlike the acrylic polyol resin cured by functional group reaction, in the present invention, the acrylic polyol resin cured by free radical reaction with a catalyst-promoter (which is an oxidation-reduction system) synthesized by block copolymerization of n-BMA monomer, styrene monomer and HEMA or HEA monomer has excellent UV resistance and weather resistance, while the technical parameters and mechanical properties meet the requirements for use in artificial stone products. When applied to the manufacture of quartz-based artificial stone samples, the UV resistance and weather resistance of the acrylic polyol resin cured by free radical reaction of the present invention are also confirmed. This confirms that the acrylic resin cured by free radical reaction of the present invention fully meets the requirements for application in quartz-based artificial stone production technology.

Claims

1. A heat-curable hydroxyl-containing acrylic resin composition (acrylate polyol resin) that cures by free radical reaction with a catalyst-accelerator as an oxidation-reduction system for use in the manufacture of artificial stone to enhance UV resistance and weather resistance, wherein the composition comprises: (a) an acrylic polyol resin having UV radiation resistance and weather resistance, which is synthesized from monomers of n-butyl methacrylate (n-BMA), styrene, hydroxyethyl methacrylate (HEMA) or 2-hydroxyethyl acrylate (HEA) using the following component ratios: (i) n-BMA in the range of 51.5% to 60.5% by weight, (ii) styrene in the range of 5.0% to 15.5% by weight, (iii) HEMA or HEA in the range of 33.5% to 45.6% by weight, (iv) a synthesis reaction initiator in the range of 0.01% to 2% by weight, the synthesis reaction initiator being selected from the following: dibenzoyl peroxide or di-tert-butyl peroxide or azobisisobutyronitrile or a combination thereof, calculated by the total weight of the reaction mixture; (b) a curing catalyst, which is an organic peroxide compound selected from the following: tert-butyl peroctanoate; tert-butyl peroxybenzoate; tert-butyl peroxy-3,5,5-trimethylhexanoate; tert-butyl peroxy-pivalate; tert-butyl peroxy-2-ethylhexanoate; tert-butyl peroxy-isobutyrate; tert-butyl monoperoxy-maleate; tert-butyl peroxy-neoheptanoate; tert-butyl peroxy-neodecanoate; di(4-methylbenzoyl)peroxide; dilauroyl-peroxide; 2,5-dimethyl-2-5-di(2-ethylhexanoylperoxy)hexane; di(3,5,5-trimethyl-hexanoyl)peroxide; tert-amyl peroxy-neodecanoate; 1,1,3,3-tetramethylbutyl peroxy-neodecanoate or a combination thereof, calculated by the weight of the acrylic polyol resin in the range of 0.1 to 5% by weight; (c) a curing accelerator selected from the following: a cobalt (II) salt compound, preferably cobalt (II) octoate, or a manganese salt, in the range of 0.005% to 1% by weight calculated by the weight of the acrylic polyol resin.

2. The heat-curable acrylic polyol composition according to claim 1, wherein the finished acrylic polyol composition has the following physical and mechanical properties: i) a solids content in the range of 40% to 80%; ii) Color according to Hazen scale ≤ 10; iii) Liquid density is between 1.01 and 1.2 g / cm at a temperature of 23°C and a relative humidity of 57%. 3 within the scope of iv) a viscosity in the range of 600 to 3000 mPa.s at a temperature of 23°C; v) a tensile strength in the range of 40 to 60 MPa; vi) a flexural strength in the range of 60 to 120 MPa; vii) Barcol hardness in the range of 40 to 55; viii) resistance to ultraviolet radiation and weathering, wherein the color change index ΔE≤2.

3. Artificial stone products, which are composed of: (a) a matrix phase of the acrylic polyol resin according to claim 1 in a range of 5 to 20% by weight; (b) the reinforcing agent is an inorganic granular aggregate, in the range of 80% to 95% by weight, wherein the inorganic granular aggregate comprises: Quartz granular aggregate, cristobalite, sand and sand or glass derivative materials with a particle size of ≤ 0.045 mm, in the range of 10% to 37.5% by weight, Quartz granular aggregate, cristobalite, sand and sand or glass derivative materials with a particle size of 0.045 mm to 0.1 mm, in the range of 15% to 42.5% by weight, Quartz granular aggregate, cristobalite, sand and sand or glass derivative materials with a particle size of 0.1 mm to 0.5 mm, in the range of 10% to 37.5% by weight, Quartz granular aggregate, cristobalite, sand and sand or glass derivative materials with a particle size of 0.5 mm to 2.5 mm, in the range of 17.5% to 45.6% by weight, Quartz granular aggregate, cristobalite, sand and sand or glass derivative materials having a particle size of 2.5 mm to 6.0 mm, in the range of 20% to 47.5% by weight.

4. The artificial stone product according to claim 3, wherein the artificial stone has the following physical and mechanical properties: i) Flexural strength between 40 and 120 N / mm 2 within the scope of ii) Deep wear between 89 and 175 mm 3 within the scope of iii) a water absorption rate in the range of 0.01% to 0.05%; iv) Impact resistance ≥ 3J; v) UV and weather resistance, wherein the discoloration index ΔE*≦2 after 1000 hours of UV exposure in the UV test.

Citation Information

Patent Citations

  • Thermosetting acrylic resin for powder coating as well as synthesis method and applications of thermosetting acrylic resin

    CN103613698A

  • High solids acrylic-based coatings

    US4985517A